Effect of fly ash particle size on thermal and mechanical properties of fly ash-cement composites - Bicer, Ayse (Elsevier, 2018)
In this study, fly ash was used in concrete and plaster in place of sand and the impact of fly ash grain size on thermal and mechanical performance of composite material was examined. Fly ash used in the experiments was received from Soma Thermal Power Station and separated into the various grain size groups namely unsieved, > 75 x 10(-6) m, (45-75) x 10(-6) m and < 45 x 10(-6) m. In all fly ash and cement mixtures, the weight percentages of fly ash were accepted as 10, 30, 50, 70 and 90%. Cement IV/B (P) 32.5 R was used as the binding material and 20 specimens were prepared according to the grain diameter and percentage of fly ash. Some tests were performed using the new products to find out their detailed properties including density, thermal conductivity, compressive tensile strength, and elasticity module and water absorption. It was found in the experiments that (i) as the grain size diameter decreased, ash density increased 16.12%, and porous structure was replaced by full-grain ash and its color turned to light brown; (ii) as the ash addition ratio increased 10-90% in fly ash cement mixtures, thermal conductivity coefficient and compressive strength values decreased in the rates of 14.47-24.52% and 1.25-9.4% respectively; (iii) concrete or plaster turned into an insulator due to fly ash.
Keywords: Fly ash; Light concrete; Insulation plaster; Waste management